Spanning boundaries and disciplines university technology commercialization in the idea age - Libecap, Gary D.; Thursby, Marie; Hoskinson, Sherry (Emerald, 2010)
Successful technology commercialization requires the integration of multiple perspectives and collaboration of experts from very different backgrounds. More often than not, key individuals in the process reside in different organizational units--each with their own mission, agendas, and cultures. This volume addresses the challenges that can arise when individuals from technical, business, and legal environments must converge on the goal of commercialization. Specifically, it brings together studies from organizational behavior, marketing, economic, and sociological perspectives on commercialization of university technologies. Chapter foci range from theoretical research on academic entrepreneurship, multidisciplinary student team management conflicts such as background, purpose, communication, and learning style, to a patent data examination of sociological factors in technology paths in nanotechnology innovation. New results are presented on career goals of PhD scientists and engineers highlighting their desire for education providing skills from these other domains. Educational responses such as cross disciplinary team models, as well as multidisciplinary entrepreneurship centers and specialized masters programs for scientists are presented.
Keywords: Economic development -- Effect of education on.; Academic-industrial collaboration.; Technology transfer -- Economic aspects.; elektronické knihy; electronic books